UAN eSports (2024)
The present project focused on optimizing the visibility and impact of the eSports program at Universidad Antonio Nariño (UAN) in its Bogotá campuses, through a redesign of its visual identity and the implementation of communication strategies. The general objective was to strengthen the gamer culture within the university community, enhancing the sense of belonging and recognition of the program.